Existential structures as specialised constructions - Vince Liégeois; Laurent Gautier (ELAD-SILDA, 2025)
This constructionist paper deals with the specialised manifestations that constructions can exhibit and considers two questions: (i) how such specialised manifestations can be linked back to the cognitive architecture of the domain, (ii) whether we can, in this regard, speak about specialised constructions, for which (a) domain-related features regarding form and meaning, and (b) their location within the constructicon will be considered in more depth. More specifically, this study looks at a pilot corpus of Flemish weather reports (domain: meteorology) and performs a corpus-based analysis of existential constructions (Dt. er is/zijn; het is; het wordt) as a case-study. The results of this corpus-based analysis provide deeper insights into the lexicological features of the texts and the ways in which the constructions align with the discourse patterns of this specialised text genre.